Impact of Newspaper Characteristics on Reporters' Agricultural Crisis Stories: Productivity, Story Length, and Source Selection - Judith M. White; Tracy Rutherford (Journal of Applied Communications, 2012)
This study examined coverage of the December 2003 bovine spongiform encephalopathy (BSE) event to discover differences in sources used by reporters based on their employing newspapers’ geographical location, circulation and ownership type. Sixty-two stories dealing with the first U.S. bovine spongiform encephalopathy incident were subjected to content analysis. Stories – published from December 23, 2003 to October 31, 2004 – were selected through a keyword search from U.S. newspapers included in the LexisNexis database. These stories were divided into two equal groups based on reporters’ work-role identity and were analyzed by length, number of sources, and source variety and the employing newspapers’ geographical location, circulation and ownership type. ANOVA and bivariate correlation were among statistical analysis techniques used.
Keywords: mad cow; BSE; reporters; sources; newspapers